INNOVATIVE TECHNOLOGIES FOR TRAINING NURSING STAFF ON THE EXAMPLE OF DAY-CARE CLINIC OF HIGH TECHNOLOGY - E. G. Biryukova; E. Yu. Varfolomeeva (Union of pediatricians of Russia, 2012)
The article analyzes the development of medical and organizational measures aimed improving the efficiency of nurses at the example of a day -care clinic. The paper analyzes the innovative approaches in children's day-care nurses. New economic conditions call for new approaches to the organization and structure of health care, implementation of nursing innovations.